Stimulation of motor skills through game models in early childhood and elementary school students: systematic review in Indonesia - Didi Suryadi; Ahmad Nasrulloh; Novi Yanti; Ramli Ramli; Lazuardy Akbar Fauzan; BM. Wara Kushartanti; Sumaryanti Sumaryanti; Bernadeta Suhartini; Eka Swasta Budayati; Novita Intan Arovah; Mashud Mashud; Mikkey Anggara Suganda; et al. (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Background and purpose of the study. The relevance of motor skills for every student since they have benefits and affect the overall development of kids. Several studies have offered data on learning and developing motor abilities in youngsters. The game model's information is extensively created and utilized as a reference to enhance gross motor abilities. As a result, the purpose of this study is to conduct a review of the scientific literature in Indonesia on the stimulation of motor skills in early childhood and primary school students through learning using game models. The Harzing Publish or Perish tool was utilized for the search in this study. A database (Scopus) was utilized to find publications on motor skill development through play-based learning. The search was carried out in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) recommendations. Only five items remained after the exclusion criteria were applied. The findings indicate that the research methods employed in cooperative learning research in Indonesia are various, including quantitative, mixed research (quantitative and qualitative), and development. On average, measuring equipment was utilized to collect data for the study. According to the findings of this review, in the first group, traditional play-based children's learning is capable of optimizing kindergarten children's basic motor development, with a track record of implementing the concept/theoretical basis, activity stages, social systems, reaction principles, support systems, and impact models, and increasing students' basic skills for high motor skills. In the second category, learning structured in the form of games may stimulate children's fine motor and cognitive abilities, as well as strengthen fundamental motor skills and build gross motor skills for use in the learning process. Some shortcomings in the review have been identified, and it is important to continue this study internationally with a literature review or mapping study (bibliometric and scientometric), as well as to conduct research on the use of the game model and its impact.